2017
DOI: 10.1021/acs.iecr.7b02690
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Amidoxime-Grafted Activated Carbon Fibers for Efficient Recovery of Uranium(VI) from Aqueous Solution

Abstract: A novel fibrous sorbent, amidoxime-grafted activated carbon fibers (ACFs-AO), was prepared using a chemical grafting method and tested for the efficient removal of uranium from aqueous solution. The sorbent was characterized using X-ray photoelectron spectroscopy, field-emission scanning electron microscopy, elemental analysis, thermogravimetric analysis, and Brunauer–Emmett–Teller. The effects of pH, contact time, initial concentration, and temperature on the sorption of U­(VI) were investigated. The sorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…The first weight loss before 160 °C was ascribed to the evaporation of physically absorbed water. The second weight loss from 160 to 350 °C could be the decomposition of the amidoxime groups [26,41,42]. The third decomposition from 350–500 °C could be regarded to the decomposition of the main chain of PAO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first weight loss before 160 °C was ascribed to the evaporation of physically absorbed water. The second weight loss from 160 to 350 °C could be the decomposition of the amidoxime groups [26,41,42]. The third decomposition from 350–500 °C could be regarded to the decomposition of the main chain of PAO.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, with regard to the practical application of various adsorbents in seawater, more active chelating sites, more feasible materials synthesis along with less cost are critical factors for the design of the optimal adsorbent towards high efficiency [23,24,25,26]. From this point, aerogels as highly porous materials with extremely high specific surface area (SSA) (~1000 m 2 ·g −1 ) and high porosities (~99%) satisfy the above requirements exactly [27,28,29,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The deprotonation of reactive groups (which facilitates the tautomerization effect), the progressive formation of neutral (for zirconium(IV)) or polynuclear species (for uranium(VI)) explains the progressive increase in sorption properties. This is consistent with the results reported for uranium(VI) sorption on amidoxime‐functionalized sorbents . In the case of seawater, uranium is negatively charged (being under the form of carbonate species) which can be readily sorbed by positively charged amidoxime‐functionalized polymers .…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the results reported for uranium(VI) sorption on amidoxime-functionalized sorbents. 26,34 In the case of seawater, uranium is negatively charged (being under the form of carbonate species) which can be readily sorbed by positively charged amidoxime-functionalized polymers. 33 Wei et al 55 reported the interest of bi-functionality of polymer sorbents on the recovery of uranium from complex solutions: the presence of uranyl carbonate species may be bound by positively charged reactive groups while neutral species can be bound by chelation on amidoxime groups.…”
Section: Sorption Studies Ph Effectmentioning
confidence: 99%
See 1 more Smart Citation